Smoking habit as a risk factor in tuberculosis: a case-control study - Sahiratmadja, Edhyana; Nagelkerke, Nico (Universa Medicina, 2011)
Indonesia is fifth in the tuberculosis (TB) prevalence globally and this country is one of the largest tobacco producers. Smoking has been reported to be an important risk factor for TB and a reduction in smoking could be expected to have a significant impact on TB incidence and prevalence. However, studies from various countries yielded conflicting results. Our study aims to explore the association between smoking and TB in Indonesia as TB-endemic country. In two major cities of Indonesia, Jakarta and Bandung, a case-control study had been conducted. TB was diagnosed based on WHO criteria including clinical presentation, and chest X-ray (CXR) examination, and confirmed by microscopic detection of acid-fast bacilli in Ziehl-Nielsen stained sputum smears or by culture of M. tuberculosis. Newly diagnosed smear-positive pulmonary TB patients (n=802) and their spouses (n=253) or sex-matched neighborhood controls (n=534) were interviewed about their smoking habits. An extensive questionnaire was used to collect data about smoking habits of both patients and controls. Smoking categories were grouped into ever (for current/past smokers) and never. Our study result showed that smoking appears not to be strongly associated with TB (OR=0.99, 95% CI 0.76-1.31). The reasons for the effect heterogeneity remain to be elucidated as smoking is a lethal habit and should be well controlled. The need to incorporate tobacco cessation programs into TB treatment is strongly recommended to improve TB control.